Dampak Pernikahan Dini Terhadap Manajemen Keuangan Keluarga Dalam Islam - Kamila, Nurul; Sunariyah, Anik; Hipni, Mohammad; Mawardi, Imam (LPPM STAI Muhammadiyah Probolinggo, 2024)
Early marriage is often a choice for some couples, either due to social, cultural or economic factors. However, getting married without financial readiness and adequate understanding of financial management can have a significant impact on family welfare. In Islam, family financial management must comply with sharia principles which emphasize balance, responsibility and avoidance of usury. This research aims to analyze the impact of early marriage on family financial management in Islam. The method used in this research is a qualitative method with a descriptive approach. The results of this research show that early marriage can cause unstable income, difficulty in controlling expenses and difficulty in saving. Couples who marry at a young age also tend not to carry out good financial planning and thus become trapped in debt. This is due to their young age and lack of experience and education. In the context of financial management in Islam, early marriage can lead to excessive consumption patterns and low sharia financial literacy. Keywords: Early Marriage, Family Financial Management, Islam.